Performance Analysis of Highly EfficientPhotocatalytic Activity of gC3N4/ZnxCd1-xS Com Posites - TIAN Yan; TAN Yu; ZHANG Zehua; TONG Yanmin; QI Shuyan (Journal of Harbin University of Science and Technology)
In this paper, insitu growth technique was used, and gC3N4/ZnxCd1-xS heterojunction photocatalyst was prepared by coprecipitationhydrothermal method The structure and photochemical properties of the photocatalyst were characterized by XRD, SEM, TEM, EDS and UVVis DRS Photocatalytic activity of gC3N4/ZnxCd1-xS was evaluated by degradation of methylene blue (MB) under visible light irradiation The mechanism of photocatalytic degradation was studied by capture agent test The results show that gC3N4 and ZnxCd1-xS form a wellcrystallized heterojunction structure, and as the value of x increases, the light absorption range of the heterojunction gradually decreases Among them, gC3N4/Zn05Cd05S have the best photocatalytic performance After 210 minutes of visible light irradiation, the degradation rate to MB reached 99% After 4 reproducibility tests, there was no significant decrease in photocatalytic activity Through the capture agent experiments, the main active substances involved in degradation are h+ and O-2·